The Role of Social Media Benefits in Affecting Purchase Intention to Reserve a Liveaboard Phinisi Trip in Labuan Bajo - Rizkiyana, Raiza (Integrasi Sains Media, 2023)
Tourism has emerged as a key driver of economic growth, leading to a significant emphasis on maximizing consumption within the industry. Bali, as one of Indonesia's prominent tourism destinations, is renowned for its natural beauty and rich culture, attracting not only domestic travelers but also tourists from around the world. Recognizing the global popularity of Bali, the Indonesian Ministry of Tourism and Creative Economy launched the '10 Bali Baru' program, aiming to promote and enhance the appeal of ten other local tourist destinations to rival Bali's success. Among these destinations is Labuan Bajo, which offers tropical landscapes and a unique experience with Liveaboard Phinisi trips. This study focuses on bolstering the tourism industry in Labuan Bajo through social media marketing efforts that can attract tourism consumers' intention to book Liveaboard Phinisi tours. To achieve this, a quantitative approach was employed, gathering data from over 200 survey respondents in Indonesia and conducting data analysis using PLS-SEM. The research findings offer valuable marketing insights to increase purchase intention for domestic tourism products through effective social media marketing strategies.